Coping amongst elite-level sports coaches: A systematic review - Olsen, M. G.; Haugan, J. A.; Hrozanova, M.; Moen, F. (International Sport Coaching Journal, 2021)
The current study presents a systematic review of six empirical research studies that have explored coping amongst elite-level sport coaches. The study was carried out employing Fletcher et al.`s meta-model of stress, emotions, and performance as a basis for the review. The present results clearly revealed that, despite being an important aspect of coaches` functioning, coping is almost never researched in its full complexity, and scarce attention is given to cognitive appraisals and long-term outcomes. To our knowledge, current research has so far been limited to the perceived stressors and employed coping strategies. Compared with problem-focused coping, emotion-focused coping is less frequently reported. Emotion-focused coping also has some limitations regarding occurrence and diversity in reported strategies. The reasons for this are not well-known due to the lack of comprehensiveness in the research. Hence, researchers are encouraged to further investigate coping amongst elite-level coaches and to do so by treating it as a concept affected by appraisals and personal and situational characteristics that exist in the context of a larger stress process.